A novel current controller in photovoltaic grid-connected inverter. (3rd April 2021) - Mao, Peng; Zhang, Mao; Zhu, Yaru; Zhang, Weiping
ABSTRACT: Current control technology is a key issue in photovoltaic grid-connected inverters. Usually, since proportional resonant (PR) control can achieve infinite gain at a certain frequency leading to zero stationary error and selective disturbance rejection as compared with PI controller, it is widely used in grid-connected inverters. In this paper, performance of system using PR controller is investigated first. The disadvantages of PR controller are as follows: (1) the disturbance introduced by voltage loop has a severe impact on quality of grid-connected current; (2) Phased Locking Loop (PLL) is essential in system. Based on degree of freedom theory, resonant-proportional (R-P) controller and resonant-proportional and resonant-proportional (RP-RP) controller are proposed to overcome the disadvantages of PR controller. Additional advantages of RP-RP controller are as follows: (1) less impact on quality of grid-connected current caused by voltage loop disturbance; (2) non-essential PLL; (3) better immunity to fluctuation of grid frequency. A detailed comparison of different controllers is also obtained. Simulation and experiment results verify the prototype's feasibility and validity.